2012
DOI: 10.1007/s00213-012-2888-5
|View full text |Cite
|
Sign up to set email alerts
|

Brain RGS4 and RGS10 protein expression in schizophrenia and depression. Effect of drug treatment

Abstract: Expression of RGS4 and RGS10 proteins at their predominant subcellular location was studied in the postmortem brain of subjects with psychiatric disorders. The results suggest unaltered membrane RGS4 and cytosolic RGS10 proteins levels in schizophrenia and major depression. Antipsychotic treatment seems to increase membrane RGS4 immunoreactivity. Further studies are needed to elucidate RGS4 and RGS10 functional status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 58 publications
1
18
1
1
Order By: Relevance
“…A significant amount of research has been devoted to looking at the role of RGS4 as a potential etiological factor for schizophrenia (Bani-Fatemi et al, 2013;Cheng et al, 2013;Gong et al, 2013;Lener et al, 2013;Monroy et al, 2013a;Rivero et al, 2013;Rose and Donohoe, 2013;Schwendt et al, 2012;Steiner et al, 2014). Postmortem studies showed lowered levels of RGS4 expression in many locations in the frontal cortex of schizophrenics, such as the superior temporal gyrus (Bowden et al, 2007).…”
Section: Rgs4mentioning
confidence: 96%
“…A significant amount of research has been devoted to looking at the role of RGS4 as a potential etiological factor for schizophrenia (Bani-Fatemi et al, 2013;Cheng et al, 2013;Gong et al, 2013;Lener et al, 2013;Monroy et al, 2013a;Rivero et al, 2013;Rose and Donohoe, 2013;Schwendt et al, 2012;Steiner et al, 2014). Postmortem studies showed lowered levels of RGS4 expression in many locations in the frontal cortex of schizophrenics, such as the superior temporal gyrus (Bowden et al, 2007).…”
Section: Rgs4mentioning
confidence: 96%
“…For example, some protein studies of RGS4 protein used antibodies that detect a band of higher molecular weight than is predicted for RGS4. 14,15 Subject characteristics that reflect both protein and mRNA quality were not reported, differed between diagnostic groups, or had values suggesting that the preservation of mRNA or protein was less than ideal in some previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…26 Although the present and previous 10-12 studies have found lower RGS4 mRNA and protein expression in the DLPFC of schizophrenia, other studies have found no differences between healthy comparison and schizophrenia subjects in the DLPFC. [13][14][15] Methodological and subject characteristics may contribute to these disparate findings. For example, some protein studies of RGS4 protein used antibodies that detect a band of higher molecular weight than is predicted for RGS4.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, immunohistochemical analysis of RGS10 protein in postmortem human brain tissue revealed that the levels of RGS10 in schizophrenia and major depression were comparable to that of healthy control subjects. 64,65 Interestingly, RGS proteins do negatively regulate G αi/o protein activity as well as μ-opioid receptor (MORs) function. In support of this possibility, the levels of RGS10 in frontal cortex of short-term opiate abusers are significantly decreased but remain relatively similar to control levels in longterm opiate abusers, 66 suggesting RGS10 may play a role in opiate tolerance, dependence, and/or withdrawal.…”
Section: Rgs10 In Pathophysiological Statesmentioning
confidence: 99%